SEM Evaluation of ECC-Porous Asphalt Gravel Mortar Composites Based on Styrofoam and Palm Shell Ash Based on Compressive Strength Tests: Evaluasi SEM terhadap Komposit Mortar ECC-Kerikil Aspal Porus Berbasis Styrofoam dan Abu Cangkang Sawit Berdasarkan Uji Tekan - Rahmawati, Lusi; Aswin , Muhammad; Nursyamsi, Nursyamsi (Academia Open, 2026)
General Background: Road pavement development requires materials with reliable mechanical performance and greater sustainability to address limitations in flexible and rigid pavement systems. Specific Background: Engineered Cementitious Composites combined with porous asphalt gravel, fly ash, palm shell ash, and styrofoam waste were investigated as alternative pavement composite materials. Knowledge Gap: The internal microstructural explanation of compressive strength behavior in ECC mortar–porous asphalt gravel composites with styrofoam and palm shell ash remains limited. Aims: This study aimed to evaluate compressive strength behavior and SEM-based microstructural characteristics of ECC mortar–porous asphalt gravel composites. Results: Compressive testing at three days showed that the composite without styrofoam reached the highest compressive strength of 7.351 MPa, while the styrofoam-based composite reached a maximum of 5.360 MPa. SEM observations showed that the non-styrofoam composite had a relatively denser ECC mortar matrix with fewer pores and micro-gaps. In contrast, the styrofoam-based composite showed a more heterogeneous microstructure dominated by pores, voids, and microcracking, particularly in the aggregate–mortar interface transition zone. Novelty: This study links SEM microstructural evidence with compressive strength behavior in ECC mortar–porous asphalt gravel composites using fly ash and palm shell ash. Implications: The findings indicate that fly ash and palm shell ash can support sustainable pavement material development, while polymer waste addition must be controlled to prevent excessive mechanical performance loss. Highlights: Non modified specimens reached 7.351 MPa after three days. Polymer additive specimens reached a maximum of 5.360 MPa. Interface voids and microcracks explained weaker mechanical behavior. Keywords: Palm Kernel Shell Ash, ECC, Porous Asphalt, Polystyrene, Compressive Strength, SEM